Planting Productive Seeds Based on Watersheds in Order to Welcome World Environment Day in Kelambir V Kampung Village, Hamparan Perak Region, Deli Serdang District - Khairani, Siti; Harahap, Siti Nurlani; Simbolon, Heri Yusuf; Sari, Dini Novita; Sembiring, Juhardi; Fahri, Romi; Utami, Khairuna; Depari, Nelfita Rizka S; Sembiring, Riani Sari (Talenta Publisher, 2023)
Community service for planting productive tree seedlings based on watersheds (DAS) in order to welcome world environment day, aims to socialize the importance of a good environment for life; cooperate with the village government and the Sejahtera Tani farmer group; introducing the types of productive tree seedlings; planting productive tree seedlings with the village government and the Sejahtera Tani farmer group. This community service activity was carried out in Kelambir V Village, Hamparan Perak District, Deli Serdang Regency, North Sumatra Province. This activity is a form of implementation of one of the tridharma of Higher Education, especially community service by the UNUSU academic community, as well as in the framework of UNUSU's participation in the effort to plant watershed-based productive seeds in order to welcome World Environment Day. The method of implementing community service is carried out in 3 stages, namely the preparation stage, the implementation stage and the reporting stage. During the preparatory phase, socialization was carried out, determining socialization areas, identifying needs, coordinating with relevant village officials, preparing proposals and completing supporting documents. In the implementation phase, declaration is carried out, planting productive DAS-based seeds, socializing planting productive DAS-based seeds, monitoring, at the reporting stage, namely compiling a final report on community service activities. The result of this community service activity is planting productive trees around the watershed and in the gardens of farmer groups, which total 100 productive tree seeds including matoa, simpur, jamblang, duku, rambutan, longan, tamarind seeds.